Chemerin-9, a potent agonist of chemerin receptor (ChemR23), prevents atherogenesis. (20th August 2019) - Sato, Kengo; Yoshizawa, Hayami; Seki, Tomomi; Shirai, Remina; Yamashita, Tomoyuki; Okano, Taisuke; Shibata, Koichiro; Wakamatsu, Miyu J.; Mori, Yusaku; Morita, Toshisuke; Matsuyama, Taka-aki; Ishibashi-Ueda, Hatsue; et al.
Abstract: Plasma levels of chemerin, an adipocytokine produced from the adipose tissues and liver, are associated with metabolic syndrome and coronary artery disease (CAD). Chemerin and its analog, chemerin-9, are known to bind to their receptor, ChemR23. However, whether chemerin and chemerin-9 affect atherogenesis remains to be elucidated. We investigated the expression of chemerin and ChemR23 in human coronary arteries and cultured human vascular cells. The effects of chemerin and chemerin-9 on atheroprone phenomena were assessed in human THP1 monocytes, human umbilical vein endothelial cells (HUVECs), and human aortic smooth muscle cells (HASMCs) and aortic lesions in Apoe −/− mice. In patients with CAD, a small amount of ChemR23, but not chemerin, was expressed within atheromatous plaques in coronary arteries. Chemerin and ChemR23 were expressed at high levels in THP1 monocytes, THP1-derived macrophages, and HUVECs; however, their expression in HASMCs was weak. Chemerin and chemerin-9 significantly suppressed the tumor necrosis factor-α (TNF-α)-induced mRNA expression of adhesion and pro-inflammatory molecules in HUVECs. Chemerin and chemerin-9 significantly attenuated the TNF-α-induced adhesion of THP1 monocytes to HUVECs and macrophage inflammatory phenotype. Chemerin and chemerin-9 suppressed oxidized low-density lipoprotein (oxLDL)-induced macrophage foam cell formation associated with down-regulation of CD36 and up-regulation of ATP-binding cassette transporter A1 (ABCA1). In HASMCs, chemerin and chemerin-9 significantly suppressed migration and proliferation without inducing apoptosis. In the Apoe −/− mice, a 4-week infusion of chemerin-9 significantly decreased the areas of aortic atherosclerotic lesions by reducing intraplaque macrophage and SMC contents. Our results indicate that chemerin-9 prevents atherosclerosis. Therefore, the development of chemerin analogs/ChemR23 agonists may serve as a novel therapeutic target for atherosclerotic diseases.